Complete response to temozolomide in chronic lymphocytic leukemia. Issue 7 (31st May 2017) - Rao, Archana; Ramani, Nisha; Stoppacher, Robert; Coyle, Thomas
Key Clinical Message: We report a case of incidentally diagnosed chronic lymphocytic leukemia (CLL) in a patient with glioblastoma, which responded completely following standard treatment of the glioblastoma with temozolomide and cranial irradiation. The patient remained without an evidence of CLL until his death from recurrent glioblastoma. Further study of temozolomide for the treatment of CLL is indicated. Abstract : We report a case of incidentally diagnosed chronic lymphocytic leukemia (CLL) in a patient with glioblastoma, which responded completely following standard treatment of the glioblastoma with temozolomide and cranial irradiation. The patient remained without an evidence of CLL until his death from recurrent glioblastoma. Further study of temozolomide for the treatment of CLL is indicated.